Practice Matters: Pro-environmental Motivations and Diet-Related Impact Vary With Meditation Experience - Thiermann, Ute B.; Sheate, William R.; Vercammen, Ans (Frontiers in Psychology, 2020)
Mindfulness has emerged as a potential motivator for sustainable lifestyles, yet few studies provide insight into the relationship between mindfulness practice levels and individual engagement in pro-environmental behaviors. We also lack information about the significance of meditators’ behavioral differences in terms of their measurable environmental impact and the motivational processes underlying these differences in pro-environmental performance. We classified 300 individuals in three groups with varying meditation experience and compared their pro-environmental motivations and levels of animal protein consumption. Exceeding prior attempts to compare high-impact behaviors of mindfulness practitioners and non-practitioners, we created the most detailed classification of practice engagement by assessing frequency, experience and type of meditation practice. This nuanced view on mindfulness practice reveals that advanced meditators, who reported high levels of connectedness with nature, subjective happiness and dispositional mindfulness showed significantly more concern for the environment. They also demonstrated the lowest levels of greenhouse gas emissions, land occupation and water use related to their animal-protein consumption. This study is the first to follow a self-determination theory perspective to deepen our understanding of the motivational differences between meditator groups. We revealed that advanced meditators reported significantly more integrated motivation towards the environment than non-meditators. We also provided preliminary evidence for a new theoretical framework suggesting that experiential strategies such as mindfulness practices could strengthen the relational pathway of pro-environmental behaviors. Using sequential mediation analysis, we confirmed that the negative effect of mindful compassion practice on greenhouse gas emissions from animal-protein consumption is partially mediated by connectedness with nature and integrated motivation towards the environment. While our study does not support assumptions of causality, it shows that much can be learned by studying the motivations of advanced meditators for maintaining high levels of pro-environmental behavior.